(untitled) (World Bulletin of Public Health, 2022)
On the material of 60 cases of patients with different purulent-inflammatory diseases of maxillofacial region having hepatitis B . This article demonstrates the severity of the course and high prevalence of acute inflammatory process in the maxillofacial region, as well as the necessity of pathogenetic therapy of hepatitis B in the complex treatment of the discussed group of patients